A atuação do secretário executivo no setor público: o caso da Universidade Federal do Ceará - Ferreira, Francisca Daniele (2011)
The globalization challenged the social organizations, which have to stabilish modern standards of management. This fact modifies the culture of the institutions, the public service being also trying to adapt itself to this reality. Under this perspective are the Executive Secretariate professionals, which are evoling in their way to act and, recently, started to enter the public institutions through contests. This research focuses in their way of acting in these organizations, more specifically in the Federal Universities of Higher (IFES), having locus the Federal University of Ceará (UFC). Therefore, the general purpose of this study was to investigate the performance of the executive secretaries at the UFC, identifying in which ways their work contributes to improve the management performance in the institution, considering the available management tools. The specific objectives were to describe the attributions of the executive secretaries at the UFC, identify the positive points and the difficulties, also analyze their performance under the manager’s point of view, verify if they satisfy the expectations of the institution. As a methodological procedure, this research is descriptive and the technical procedures adopted to collect data were the bibliographic, documental and field analysis using questionnaires and interviews. The participants were the executive secretaries and the managers of the UFC in a stratified sample. For the analysis and interpretation of data categories were used that sought to understand the meanings in the responses obtained during the interviews and questionnaires. The results offer information to reach the proposed objectives and identify the way of acting of the executive secretaries, the positive points and the difficulties faced by them and the positive vision that the managers have about the professionals that work in the institution. After analyzing the results, it was felt that greater publicity is needed for the profession and institution managers as a whole, to avoid misunderstandings or underuse of the professional in what concerns the delegation of activities and responsibilities. It was also realized that the insertion of the executive secretaries at the UFC had not only positive aspects for the institution, but also and the possibility of discussion about the need for new hires, given the number of environments that do not have executive secretaries.